The effect of relaxation exercises on some variables Physiology and accuracy of aiming with pneumatic weapons Experimental research on advanced archery players with (air gun) (Journal of the College of Basic Education, 2022)
The effect of relaxation exercises on some psychological alterationsand aiming precision with air weapons(the gun) Experimental ResearchResearcher: Agharied Salim The aims of this research consist of acknowledging the effect ofRelaxation alterations in the athletes of the rifle national team, aside fromacknowledging the effect of relaxation exercises on aiming precision onthe athletes of the riflery national team (the rifle). The assumption of this research: There are assumptions of statisticalindication between the two before and after experiment on all alterationsand for the benefit of the after experiment. The sample of this research consisted of (10) pro athletes in rifelry. AndIn the light of the research results we have come to the following:1. The relaxation exercises lead to an improvement in the psychologicalalterations for the research sample.2. Relaxing exercises lead to improvement in aimingprecision for the research sample. The research recommends the necessity of relaxat